EDUKASI DAN PENDAMPINGAN KONSERVASI TERUMBU KARANG DAN MANGROVE SEBAGAI UPAYA PELESTARIAN EKOSISTEM PESISIR DI LOLIBU, KECAMATAN LAKUDO, KABUPATEN BUTON TENGAH - La Ode Muhammad Hasrul Adan; Muhammad Rais (JICS : Journal Of International Community Service, 2025)
This community service program aims to increase awaren ess and participation among coastal communities in preserving coral reef and mangrove ecosystems. Coastal ecosystems play an esse ntial role in maintaining environmental balance, supporting commun ity livelihoods, and protecting coastal areas from erosion and climate ch ange impacts. However, destructive fishing practices and uncontrol led mangrove logging still pose major threats to this region. The program involved socialization, environmental education, mangrove planting training, coral reef conservation mentoring, and ongoing co mmunity monitoring. Conducted over three months, the activities eng aged local fishermen, community leaders, women’s groups, & studen ts. Results show an 85% increase in community understanding of the importance of coastal ecosystems and the establishment of the “Saha bat Pesisir Lolibu” conservation group committed to sustainab le coa stal management. This activity demonstrates that participatory educa tion & mentoring can effectively enhance ecological awareness and promote long-term preservation of coastal resources.